Elaidyl-sulfamide, an oleoylethanolamide-modelled PPARα agonist, reduces body weight gain and plasma cholesterol in rats - Juan Manuel Decara; Miguel Romero-Cuevas; Patricia Rivera; Manuel Macias-González; Margarita Vida; Francisco J. Pavón; Antonia Serrano; Carolina Cano; Nieves Fresno; Ruth Pérez-Fernández; Fernando Rodríguez de Fonseca; Juan Suárez (The Company of Biologists, 2012)
SUMMARY We have modelled elaidyl-sulfamide (ES), a sulfamoyl analogue of oleoylethanolamide (OEA). ES is a lipid mediator of satiety that works through the peroxisome proliferator-activated receptor alpha (PPARα). We have characterised the pharmacological profile of ES (0.3-3 mg/kg body weight) by means of in silico molecular docking to the PPARα receptor, in vitro transcription through PPARα, and in vitro and in vivo administration to obese rats. ES interacts with the binding site of PPARα in a similar way as OEA does, is capable of activating PPARα and also reduces feeding in a dose-dependent manner when administered to food-deprived rats. When ES was given to obese male rats for 7 days, it reduced feeding and weight gain, lowered plasma cholesterol and reduced the plasmatic activity of transaminases, indicating a clear improvement of hepatic function. This pharmacological profile is associated with the modulation of both cholesterol and lipid metabolism regulatory genes, including the sterol response element-binding proteins SREBF1 and SREBF2, and their regulatory proteins INSIG1 and INSIG2, in liver and white adipose tissues. ES treatment induced the expression of thermogenic regulatory genes, including the uncoupling proteins UCP1, UCP2 and UCP3 in brown adipose tissue and UCP3 in white adipose tissue. However, its chronic administration resulted in hyperglycaemia and insulin resistance, which represent a constraint for its potential clinical development.